Salivary Amylase as a Predictive Marker for Radiation-Induced Salivary Dysfunction in Head and Neck Cancer: A Pilot Study - Arnadi R Shivashankara; Paul Simon; Saira Pais; Raees Tonse; Sucharitha Suresh; Manjeshwar Baliga (Middle East Journal of Cancer, 2023)
Background: Reports correlating changes in salivary flow rate and amylase with radiation dose to parotid glands and development of salivary dysfunction for Head and Neck cancers (HNC) are lacking. In the current study, an attempt was made at understanding this.Method: This was a prospective study carried out on people newly diagnosed with HNC requiring curative radiotherapy of more than 60 Gy. The salivary flow rate and levels of salivary α-amylase were evaluated before the start of radiation [day 1, before exposure to the first fraction of 2 Gy radiation], after 2 Gy [24 hours after the 1st fraction of 2 Gy, before exposure to 2nd fraction of 2 Gy on day 2 of the treatment], and on the completion of 30 Gy [(15 fraction of 2 Gy), before start of the 16th fraction, at the start of the fourth week on day 22] of radiation and development of salivary dysfunction was evaluated on a weekly basis. The demographic data were subjected to frequency and percentage, while biochemical data were stratified depending on dose to parotids and subjected to unpaired “t-test”. We also employed chi square/Fishers exact test to ascertain changes in the number of patients developing various degrees of salivary dysfunction on a weekly basis. A P value of <0.05 was considered significant.Results: Radiation decreased salivary flow rate from 0.29 ± 0.02 to 0.20 ± 0.04 (P = 0.0001) and amylase from 147.69 ± 11.15 to 109.07 ± 23.21 U/L (P = 0.0005). Both salivary flow rate and amylase was less in patients with severe salivary gland dysfunction (P = 0.014) and cumulative dose of radiation to the parotid glands (P = 0.014). The number of patients with a severe degree of salivary dysfunction was seen in people exposed to more than 25 Gy to the parotids (P = 0.04).Conclusion: The results suggested that the evaluation of salivary amylase on day 22 could be a useful predictive marker to understand the development of radiation-induced dysfunction in patients with curative radiotherapy for their head and neck cancer.